2018
DOI: 10.1149/08613.0141ecst
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Oxygen Transport Resistance for Different Types of Ionomer in PEFC Catalyst

Abstract: To improve the performance of polymer electrolyte fuel cells (PEFC), it is important to reduce the oxygen transport resistance in the cathode catalyst layer (CL). The authors have been conducted detailed analysis of the oxygen transport resistance elements: the diffusion resistances in the CL pores, the dissolution resistance into the ionomer, and the transport resistance at the Pt surface. This study improved the method to determine the limiting current density in the analysis, and the cell performances with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The effective thickness of the ionomer films estimated using O 2 mass transport resistance was found to be significantly higher than that observed by transmission electron microscopy of 1-10 nm [6,7,9]. This finding suggested that the physical properties of the thin ionomer films in confinements such as water uptake and elastic modulus differed from the properties of bulk ionomer, and the additional interaction of ionomer and Pt negatively affected mass transport [6,7,9,[17][18][19][20][21][22]. In spite of the fact that the limiting current approach is widely used for PEMFCs characterization, its implementation typically requires a cell with an active area of 1-5 cm 2 and high stoichiometry of reagents to reach currents relevant for PEMFCs.…”
Section: Introductionmentioning
confidence: 84%
“…The effective thickness of the ionomer films estimated using O 2 mass transport resistance was found to be significantly higher than that observed by transmission electron microscopy of 1-10 nm [6,7,9]. This finding suggested that the physical properties of the thin ionomer films in confinements such as water uptake and elastic modulus differed from the properties of bulk ionomer, and the additional interaction of ionomer and Pt negatively affected mass transport [6,7,9,[17][18][19][20][21][22]. In spite of the fact that the limiting current approach is widely used for PEMFCs characterization, its implementation typically requires a cell with an active area of 1-5 cm 2 and high stoichiometry of reagents to reach currents relevant for PEMFCs.…”
Section: Introductionmentioning
confidence: 84%